Immigrants assimilate as communities, not just as individuals - Timothy J. Hatton; Andrew Leigh (Institute for the Study of Labor (IZA), 2007)
There is a large econometric literature that examines the economic assimilation of immigrants in the United States and elsewhere. On the whole immigrants are seen as atomistic individuals assimilating in a largely anonymous labour market, a view that runs counter to the spirit of the equally large literature on ethnic groups. Here we argue that immigrants assimilate as communities, not just as individuals. The longer the immigrant community has been established the better adjusted it is to the host society and the more the host society comes to accept that ethnic group. Thus economic outcomes for immigrants should depend not just on their own characteristics, but also on the legacy of past immigration from the same country. In this paper we test this hypothesis using data from a 5 percent sample of the 1980, 1990 and 2000 US censuses. We find that history matters in immigrant assimilation: the stronger is the tradition of immigration from a given source country, the better the economic outcomes for new immigrants from that source
urn:nbn:de:101:1-2008042923
Keywords: 330; Einwanderung; Ethnische Gruppe; Soziale Integration; Einkommen; USA